A double blind, randomized, controlled trial to study the effect of dexmedetomidine on hemodynamic and recovery responses during tracheal extubation - Barkha Bindu; Surender Pasupuleti; Upender P Gowd; Venkateshwarlu Gorre; Radha R Murthy; M Bhanu Laxmi (Wolters Kluwer Medknow Publications, 2013)
Background: The α2-adrenoreceptor agonist, dexmedetomidine, provides excellent sedation with minimal cardiovascular instability or respiratory depression and may be a useful adjunct to facilitate smooth tracheal extubation. Materials and Methods: Fifty American Society of Anesthesiologists grade I-II patients, aged 20-45 years, scheduled for elective general surgical, urological and gynecological surgeries were studied after randomization into two groups. Group A and B, received an intravenous infusion of dexmedetomidine 0.75 mcg/kg or placebo respectively, over 15 minutes before anticipated time of end of surgery, in a double blind manner. Anesthesia techniques were standardized. Heart rate, systolic, diastolic, mean arterial pressures were recorded while starting injection, at 1, 3, 5, 10, 15 minutes after starting injection, during extubation, at 1, 3, 5 minutes after extubation, and thereafter every 5 minutes for 30 minutes. Quality of extubation was evaluated on a 5 point scale and postoperative sedation on a 6 point scale. Any event of laryngospasm, bronchospasm, desaturation, respiratory depression, vomiting, hypotension, undue sedation was noted. Results: Heart rate, systolic, diastolic, mean arterial pressures were significantly higher in group B ( P < 0.05). Extubation quality score of majority of patients was 2 in group A and 3 in group B. Sedation score of most patients was 3 in group A and 2 in group B. Bradycardia and hypotension incidences were higher in group A. One patient in group A, two patients in group B had vomiting. No patient had any other side effects. Conclusion: Dexmedetomidine 0.75 mcg/kg administered 15 minutes before extubation, stabilizes hemodynamics and facilitates smooth extubation.